2014
DOI: 10.1007/s12026-014-8557-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of SIRT1 in autoimmune demyelination and neurodegeneration

Abstract: Multiple sclerosis (MS) is a demyelinating disease characterized by chronic inflammation of the central nervous system, in which many factors can act together to influence disease susceptibility and progression. SIRT1 is a member of the histone deacetylase class III family of proteins and is an NAD(+)-dependent histone and protein deacetylase. SIRT1 can induce chromatin silencing through the deacetylation of histones and plays an important role as a key regulator of a wide variety of cellular and physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 122 publications
1
41
0
Order By: Relevance
“…In addition, studies of peripheral blood mononuclear cells (PBMCs) showed a significant decrease in SIRT1 mRNA and protein in PBMCs during relapses when compared to the levels in controls and stable MS patients. These results suggest a role for SIRT1 in MS and that modulation of SIRT1 could be a therapeutic strategy to treat MS (Martin et al, 2015; Tegla et al, 2014),…”
Section: Sirt1 – Ms and Eaementioning
confidence: 75%
“…In addition, studies of peripheral blood mononuclear cells (PBMCs) showed a significant decrease in SIRT1 mRNA and protein in PBMCs during relapses when compared to the levels in controls and stable MS patients. These results suggest a role for SIRT1 in MS and that modulation of SIRT1 could be a therapeutic strategy to treat MS (Martin et al, 2015; Tegla et al, 2014),…”
Section: Sirt1 – Ms and Eaementioning
confidence: 75%
“…Studies have confirmed that SIRT1 is extensively expressed in tissues and organs and is associated with metabolic syndrome, tumors and neurodegenerative diseases (8)(9)(10). A previous study demonstrated that icariin exerted neuroprotective effects through the induction of SIRT1, and that these effects were reversed by the use of a SIRT1 inhibitor (11).…”
Section: Introductionmentioning
confidence: 85%
“…In recent years, Sirt1 has emerged as a strategy for the treatment of multiple neurodegenerative disorders [25, 4346]. Although highly expressed in the brain, Sirt1 is also known to localize in the neurons and glial cells among various cell types [4750].…”
Section: Discussionmentioning
confidence: 99%